Diversity of Dibenzofuran-Utilizing Bacteria Isolated by Direct-Plating and Enrichment Methods - Irfan Dwidya Prijambada; Jaka Widada; Pintaka Kusumaningtyas; Dhani Suryawan (Indonesian Journal of Biotechnology, 2012)
The effect of enrichment bias on the diversity of Dibenzofuran (DBF)-degrading bacteria recovered from soil was evaluated by direct plating, plating after in-soil adaptation, and plating after batch culture enrichment. Among colonies appeared on Bushnell Haas agar with DBF as the sole carbon source, 119 colonies (49, 38, and 32 from direct plating, plating after in-soil adaptation, and plating after batch culture enrichment, respectively) were arbitrarily selected based on the appearance of the colonies. Total DNA were then extracted from the rest of the colonies and analyzed for their diversity using Ribosomal Intergenic Spacer Analysis (RISA). Number of DNA bands obtained from direct plating was higher than the ones obtained after in-soil enrichment and batch culture enrichment. The RISA bands obtained from direct plating were also found to be distributed more evenly than the ones obtained after in-soil enrichment and batch culture enrichment. Dominant bands were observed on RISA from samples obtained after in-soil enrichment and batch culture enrichment. Out of 119, only 9 isolates were consistently able to grow on Bushnell-Haas broth with DBF as the sole carbon source as indicated by broth turbidity. All of the isolates were obtained from soil samples which were enriched in a batch culture. Some of the isolates were able to degrade more then 80 % DBF in the minimal medium.